Descriptive Study of Organizational Climate in Higher Education - Karima Astari; Anissa Lestari Kadiyono; Rezki Ashriyana (Universitas Mercu Buana, 2023)
Climate is what the members of the organization experience. Organizational climate is the atmosphere surrounding the organization, uniting the characteristics of individuals, organizations, and the environment that influences the behavior of individuals in the organization. Many studies have shown that organizational climate has a significant impact on job satisfaction and employee productivity. One of which is Faculty X, a new faculty member at University Y, who wishes to examine their current organizational climate. Therefore, study on climate is an essential tool for defining and understanding organizations, providing support for future improvement. This study aims to examine organizational climate of a faculty at a private university in Bandung city, namely Faculty X at University Y. This study used a quantitative approach with descriptive research method. The sample consisted of 30 education staff employees. The instrument used was the short version of Organization Climate Scale (CLIOR), consisting of 15 items. Reliability test was carried out using Cronbach's Alpha statistical method, with the result of 0.819. The results showed that the organizational climate of Faculty X at University Y was in the high category with indicators of cooperation, work organization, relations, innovation, participation, and attachment to the job. In short, the results of this study can provide a new understanding of perception about organizational climate of Faculty X at University Y. Creating organizational climate is essential because it can overcome organizational relationships. The high organizational climate can be beneficial for Faculty X as it can influence employees’ productivity which in turn can influence the effectiveness and efficiency of the organization.